The SAGE handbook of e-learning research - Haythornthwaite, Caroline; Andrews, Richard 1953-; Fransman, Jude; Meyers, Eric M. (SAGE reference, 2016)
This is the first text of its kind to address issues in the rapidly expanding area of e-learning. It covers fundamental research questions about the entire e-learning area. Many illustrative quotations and examples make the complex philosophical concepts accessible and practically relevant